1973
DOI: 10.1159/000148832
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Rubella IgM Antibody by Indirect Fluorescent Antibody Staining, Sucrose Density Gradient Centrifugation and Mercaptoethanol Reduction

Abstract: Three methods were compared for sensitivity and specificity in detecting rubella IgM antibody in early sera from post-natal infections and in sera from congenital infections. treatment pro-Mercaptoethanol duced a significant reduction in hemagglutination-inhibiting antibody titer in only 2 of 20 sera, but sucrose density centrifugation and indirect fluorescent antibody staining with an anti-IgM conjugate demonstrated rubella IgM antibody in all 20 sera. None of the methods detected rubella IgM antibody at a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…In the present study, all results of the IPA test performed on whole serum were confirmed on serum fractions. Problems of nonspecific staining produced by low dilutions of some human sera, as reported using the I FA technique for rubella IgM detection [18]. did not interfere critically with the reading of test results.…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, all results of the IPA test performed on whole serum were confirmed on serum fractions. Problems of nonspecific staining produced by low dilutions of some human sera, as reported using the I FA technique for rubella IgM detection [18]. did not interfere critically with the reading of test results.…”
Section: Discussionmentioning
confidence: 84%
“…This method was criticized by Newman et al (1969), who found, when examining cord sera from infants with congenital rubella, that the IgM fractions were consistently contaminated with IgG which they thought might contribute to the HAI activity. Forghani, Schmidt & Lennette (1973) also detected IgG in the IgM fractions from some adult sera and suggested that this might be due to aggregation of IgG. Caul, Smyth & Clarke (1974) attempted to exclude false positive results due to contamination with IgG by titrating the HAI activity before and after treatment with 2-mercaptoethanol (2ME) which reduces IgM.…”
Section: Discussionmentioning
confidence: 99%
“…The test was simplified by Desmyter et al (1971), who examined two fractions but detected no IgM after 36 days. Forghani et al (1973) also tested only two fractions, and found specific IgM in all of 18 sera taken between 3 and 20 days after onset, and none of 10 subjects taken 1-30 years after rubella. A simplified test with only one fraction tested with and without 2ME similar to the one described here was developed by Field & Murphy (1972).…”
Section: Discussionmentioning
confidence: 99%
“…Both trailing and mixing are controlled by treating the fractions with 2ME, which shows that the inhibition is due to 337 IgM and not IgG. Forghani et al (1973) suggested that 2ME is not satisfactory for confirming IgM in fractions because reaggregation may take place, but Field & Murphy and ourselves have found no difficulty in confirming IgM in the fractions with 2ME.…”
mentioning
confidence: 90%
See 1 more Smart Citation